Data and Applications Security and Privacy XXXVI 36th Annual IFIP WG 11.3 Conference, DBSec 2022, Newark, NJ, USA, July 18-20, 2022, Proceedings - Sural, Shamik; Lu, Haibing (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book constitutes the refereed proceedings of the 36th Annual IFIP WG 11.3 Conference on Data and Applications Security and Privacy, DBSec 2022, held in Newark, NJ, USA, in July 2022. The 12 full papers and 6 short papers presented were carefully reviewed and selected from 33 submissions. The conference covers research in data and applications security and privacy.
Data Privacy -- Distributed Systems -- IoT Security -- Privacy-Preserving Access and Computation -- Quantum Security -- Security Operations and Policies.
Keywords: Data protection; Computers; Artificial intelligence; Data structures (Computer science).; Information theory; Application software; Database management; Data and Information Security; Computing Milieux; Artificial Intelligence; Data Structures and Information Theory; Computer and Information Systems Applications; Database Management System